Twentieth Anniversary Of Avegid-Aigid And The 21st Research And Development Management National Meeting, Held In 2021 (Gestión y Gerencia, 2021)
A sequence of the activities carried out by the Venezuelan Association for Research and Development Management (AVEGID) and the International Association for Research and Development Management (AIGID) is hereby presented, as well as the events that took place during the XI National Meeting of AIGID in July 2021, which Central Theme was: “Twenty Years of Research and Development Impulse in Venezuela” and a Conversation, on: "The New Working Mode Capacity". The celebration of the XX Anniversary of AVEGID-AIGID, in January 2021, was a prelude activity. The events were held virtually, due to the pandemic-endemic caused by Covid-19, as well as the presentations by students, graduates and researchers of the postgraduate degree in Research and Development Management of the Central University of Venezuela (UCV), other national and international universities and invitee speakers. Likewise, the mandatory adjustments in both associations to: unlearn, learn, undertake and continue being the open and sustainable impact research platform that they have been in their twenty years of existence.
Keywords: Research and Development Management; AVEGID; AIGID; 11st National Meeting